What Next? A Few Remaining Problems in Information Technology - Gray, Jim (1998)
Presentation: discussing the need for long-range research and the need for Universities to do some of it with the support of the government. With a discussion of the long-range systems research goals.
1998 Turing Lecture, ACM FCRC Atlanta